The Labour market under consideration of the technical changes - Sander, Tom; Teh, Phoey Lee *; Mesquita, Anabela (IGI Global, 2021)
Implementing artificial intelligence (AI) into our daily lives has created new occupations and businesses. It has changed human activities and affected individual's behaviour, influencing our decisions. This study explores the opinions of individuals about the influences of implementing AI into the labour market, especially the issue of how AI could affect human employment. There are 144 participants who responded to this survey, and the data was analysed using descriptive statistics, the t-test to identify significant differences between men and women, as well as the Spearman correlation. The results provide interesting insights and only relevant statistics and significant results are presented.